Zinc Blockade of SOS Response Inhibits Horizontal Transfer of Antibiotic Resistance Genes in Enteric Bacteria - Crane, John K.; Cheema, Muhammad B.; Olyer, Michael A.; Sutton, Mark D. (Frontiers in Cellular and Infection Microbiology, 2018)
The SOS response is a conserved response to DNA damage that is found in Gram- negative and Gram-positive bacteria. When DNA damage is sustained and severe, activation of error-prone DNA polymerases can induce a higher mutation rate then is normally observed, which is called the SOS mutator phenotype or hypermutation. We previously showed that zinc blocked the hypermutation response induced by quinolone antibiotics and mitomycin C in E. coli and Klebsiella pneumoniae. In this study, we tested whether we could induce hypermutation in a different species of enteric bacteria, Enterobacter cloacae, and whether zinc would inhibit that hypermutation response.. We then tested whether we could exploit zinc’s activity as an SOS inhibitor to block the transfer of an antibiotic resistance gene, an extended spectrum beta-lactamase (ESBL), from Enterobacter to E. coli. Zinc blocked SOS-induced development of chloramphenicol resistance in E. cloacae, and also blocked transfer of an extended spectrum ß-lactamase gene from Enterobacter to a susceptible E. coli strain. A zinc ionophore, zinc pyrithione, was 100-fold more potent than zinc salts in inhibition of ciprofloxacin-induced hypermutation in Enterobacter. Other divalent metals, such as iron and manganese, failed to inhibit these responses. Electrophorectic mobility shift assays (EMSA) revealed that zinc, but not iron or manganese, blocked the ability of the E. coli RecA protein to bind to single-stranded DNA, an important early step in the recognition of DNA damage in enteric bacteria.